PENGARUH KEMUDAHAN AKSES, KEMENARIKAN POSTING MESSAGES, DAYA TANGGAP PELAYANAN TERHADAP SIKAP KEPUTUSAN PEMBELIAN ONLINE SHOP DI INSTAGRAM - nurani, melawati (Prodi Magister Manajemen FE-UST, 2018)
The purpose of this study is to test the Effect of Ease In Access, Attraction Post Messages, Responsivenessof Customer Service Against Consumer Attitude On Decision Purchase Online Shop in Instagram. Thepopulation is yogyakarta students who buy online product shop instagram less than 3 months. The sampleused 100 students. Analytical techniques using multiple analysis techniques supported by the T test andCoefficient Determination test with the help of SPSS program for windows 16.0. The results showed thatease of access has a positive and significant influence on consumer attitudes. The attractiveness of postingmessages has a positive and insignificant effect on consumer attitudes. Responsiveness of service has apositive and significant impact on consumer attitudes. Consumer attitudes have a positive and significantinfluence on purchasing decisions. Ease of access has a negative and insignificant effect on purchasingdecisions. The attractiveness of posting messages has a positive and significant influence on purchasingdecisions. Service responsiveness has a positive and insignificant effect on purchasing decisions.Keywords: ease of access, attractiveness of message post, service responsiveness, consumer attitude,purchasing decision